2008
DOI: 10.1292/jvms.70.407
|View full text |Cite
|
Sign up to set email alerts
|

Chicken B Lymphoma DT40 Cells as a Useful Tool for in vitro Analysis of Pathogenic Infectious Bursal Disease Virus

Abstract: ABSTRACT. Susceptibility of DT40 cells to pathogenic field strains of infectious bursal disease virus (IBDV) including very virulent and classical virulent strains were studied. After the first and second passage of the virus in DT40 cells, IBDV-specific antigen was readily detected in DT40 cells inoculated with the pathogenic field strain infected bursal homogenates. Nucleotide sequence analysis in the VP2 hypervariable domain, which is critical for the virulence of IBDV, revealed no common amino acid substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Taken together, these data demonstrate that the chicken primary B cells could support the replication of cell culture-adapted and vv IBDV strains. This is in contrast to primary chicken embryo fibroblasts (CEFs) or the immortalized chicken fibroblast cell line, DF-1, which do not support the replication of vv IBDV without prior adaptation that can lead to viral attenuation [20].…”
Section: Resultsmentioning
confidence: 65%
“…Taken together, these data demonstrate that the chicken primary B cells could support the replication of cell culture-adapted and vv IBDV strains. This is in contrast to primary chicken embryo fibroblasts (CEFs) or the immortalized chicken fibroblast cell line, DF-1, which do not support the replication of vv IBDV without prior adaptation that can lead to viral attenuation [20].…”
Section: Resultsmentioning
confidence: 65%
“…A simple interpretation of our data suggests that a large proportion of the cell population is naturally resistant to IBDV infection. Low infected-cell ratios were also reported by Terasaki et al (2008) after infecting fresh DT40 cultures with several pathogenic IBDV field isolates. Data described in that report show that the number of infected DT40 cells increases significantly after three consecutive virus passages in this cell line, indicating that IBDV undergoes an adaptation process that results in the selection of variants with an enhanced ability to infect fresh DT40 cell cultures.…”
mentioning
confidence: 70%
“…In a recent report, Terasaki et al (2008) showed that very virulent IBDV isolates can be grown directly in chicken lymphoid DT40 tumour cells infected persistently with avian leukosis virus (ALV) (Baba et al, 1985), without the requirement for a preliminary adaptation process. Most importantly, serial passage in this cell line does not result in the incorporation of mutations at the specific VP2 residues.…”
mentioning
confidence: 99%
“…The surface expression of the VP3 antigen and viral RNA (based on the VP4 gene) were detected as early as 3 hpi and the peak of infection was at 12 hpi. Previous studies have shown the presence of IBDV antigen in KUL01 + bursal-derived macrophages (Khatri et al, 2005), while IBDV antigen was readily detected by IFAT in the chicken B cell line, DT40, following infection (Terasaki et al, 2008). These findings might suggest that vvIBDV is able to replicate in BM-DCs and induce their maturation indicating that recognition of vvIBDV by BM-DCs do occur and that DCs are susceptible to IBDV infection.…”
Section: Discussionmentioning
confidence: 77%